Analysis of the Role of Indonesia and Malaysia Cooperation through the General Border Committee in Handling Drug Trafficking in the Contingent in the Entikong Border - Miana Tri Lastari; Elyta Elyta; Ratu Zahirah Lutfie (International Journal of Business and Quality Research, 2023)
The General Border Committee (GBC) has played a significant role in informing collaboration between Indonesia and Malaysia in handling the issue of drug trafficking at the Entikong Border Crossing Point from 2020 to 2022. This joint effort is of utmost importance in effectively battling transnational crimes at the shared border of both nations. International crimes, including drug smuggling, human trafficking, and terrorism, have been recognized as a significant threat to the security and defense of the border region in question. The objective of this study is to analyze the collaboration between Indonesia and Malaysia, which was facilitated by the GBC, in their efforts to address drug trafficking at the PLBN Entikong border crossing between 2020 and 2021. The study utilized a qualitative research methodology with a descriptive approach. The findings of this study indicate that GBC serves as a strategic cooperation forum aimed at fostering peace, particularly along the Indonesia-Malaysia border. Its primary objective is to safely guard the border against illegal activities, including drug trafficking. The collaboration between Indonesia and Malaysia through GBC continues to evolve through regular meetings, which are designed to address and mitigate illicit drug trafficking activities, ultimately contributing to global peace. Through GBC, both countries have reached an agreement to prioritize collaboration by mobilizing their respective agencies to tackle various forms of legal violations that take place at the shared border.